Optimalisasi Kesehatan Lansia dengan Program Layanan Pemeriksaan Kesehatan Gratis di Desa Savanajaya - Annisa Cahya Madani; Khoiril Anam (Jurnal Bina Desa, 2024)
Community service in the form of free health check-up services for the elderly in Savanajaya Village, Buru Regency, is part of the work program of KKN Kebangsaan XII students. This activity aims to provide equal access to health services for all groups and increase awareness of the importance of health among the elderly. This free health check is carried out in collaboration with the Savanajaya Village Health Center and the Buru Regency Health Office. The screening process involves physical examinations and basic health tests, such as blood pressure and sugar level measurements. This program is expected to facilitate better access to health services, especially for those with economic limitations. Active community participation and collaboration between KKN students and local health agencies are key to the success of this program.